Occurrence and Distribution of Major Viruses Infecting Eggplant in Lebanon and Molecular Characterization of a Local Potato Virus X Isolate - Raied Abou Kubaa (Agriculture, 2021)
This research was carried out in order to evaluate the presence and distribution of viral infections causing severe disease in eggplant plants collected from different districts in Bekaa valley, Lebanon. Most infected plants showed virus-like symptoms consisting predominantly of leaf blotch, mottling chlorotic and ring spots; leaf twisting and plant dwarf were also observed in the visited fields. Symptomatic and asymptomatic plants were collected and screened by ELISA test for the presence of several different pathogenic viruses potentially present in the area. Results showed that potato virus Y (PVY) was the most prevalent virus found by ELISA (detected in the 15.3% of the tested plants), followed by eggplant mottled dwarf virus (EMDV, 2.9%) and cucumber mosaic virus (CMV, 1.2%), while tomato spotted wilt virus (TSWV), alfalfa mosaic virus (AMV) and pepper mottle virus (PepMoV) were not detected. Biological indexing of symptomatic ELISA-negative plants, followed by electron microscopy, indicated the presence of virus-like particles of the genus Potexvirus, which was subsequently confirmed as potato virus X (PVX) by RT-PCR and Sanger sequencing. PVX was found in 35.3% of the tested plants, all sampled in the northern Bekaa area. In a phylogenetic analysis, the partial coat protein gene sequence of a selected Lebanese isolate, PVX-AK1, clustered together with other PVX isolates from Asia. Furthermore, the 124-aa sequence of PVX-AK1 shared 100% identity with PVX-UK3, an isolate which is known as avirulent in potato genotypes carrying either Nx or Rx resistance genes. This work revealed a picture of the previously uninvestigated phytosanitary status of eggplant crops in an important horticultural area of Lebanon.